«We Should Never Write Without Feelings». Studi su William T. Vollmann. Introduzione (ENTHYMEMA, 2019)
Presentazione della sezione “«We Should Never Write Without Feelings». Studi su William T. Vollmann”.Introduction to the monographic section “’We Should Never Write Without Feelings.’ Studies on William T. Vollmann”.
Keywords: William T. Vollmann